Helping international master’s students navigate dissertation supervision: Research-informed discussion and awareness-raising activities - Harwood, Nigel; Petrić, Bojana (Journal of International Students, 2019)
Drawing on a longitudinal case study of supervisees’ and supervisors’ experiences of master’s dissertation supervision in a U.K. university, we identify prominent themes and use excerpts from our data to design pedagogic activities to use in workshops with staff and students focused on supervisory practice. The activities ask workshop attendees to consider experiential supervisory narratives involving students’ social networks, problems interpreting supervisors’ feedback, problems with differing supervisor–supervisee role expectations, and problems with supervisor–supervisee miscommunication. Each scenario is followed by our literature-informed commentary. We argue that these empirically informed, grounded awareness-raising activities will alert supervisors and supervisees to common problems experienced during supervisory journeys, and will encourage them to consider their own supervisory expectations and practices more deeply.